2023
DOI: 10.1097/qad.0000000000003540
|View full text |Cite
|
Sign up to set email alerts
|

No long-term effect of past Pneumocystis jirovecii pneumonia on pulmonary function in people with HIV

Abstract: Objective: To assess the impact of past Pneumocystis jirovecii pneumonia (PJP) on the pulmonary diffusion capacity in people with HIV (PWH) with a history of advanced immunodeficiency.Design: Prospective cross-sectional study.Methods: Adult PWH with past PJP >1 year ago were included as the study group. The control group consisted of PWH with a nadir CD4 þ lymphocyte count <200 cells/mm 3 , matched by age, sex, smoking status and time since HIV diagnosis. All PWH completed a pulmonary function test (PFT) consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Somewhat in contrast to these findings, a study by Drummond et al [1] found that a prior history of PJP contributed to abnormal spirometry but primarily to an obstructive pattern. It is difficult to compare the study to the one by Oomen et al [8] given disparate methods and differences between study populations. Could inflammation from PJP or colonization with PJP affect large and small airways in ways that promote or exacerbate chronic obstructive lung disease, without affecting long-term capacity of alveoli to transfer oxygen?…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Somewhat in contrast to these findings, a study by Drummond et al [1] found that a prior history of PJP contributed to abnormal spirometry but primarily to an obstructive pattern. It is difficult to compare the study to the one by Oomen et al [8] given disparate methods and differences between study populations. Could inflammation from PJP or colonization with PJP affect large and small airways in ways that promote or exacerbate chronic obstructive lung disease, without affecting long-term capacity of alveoli to transfer oxygen?…”
mentioning
confidence: 99%
“…The practical considerations in such a trial are problematic. However, a creative study by Oomen et al [8] attempted to answer the question by comparing two groups of PWH. The case group consisted of patients who had PJP more than 1 year previously and the control group included individuals with history of CD4 þ T-cell depletion, albeit no PJP, who were matched by age, sex, smoking history, and time since HIV diagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation